2010
DOI: 10.1080/08927014.2010.506573
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin, a potential agent to prevent biofouling of reverse osmosis membrane

Abstract: Reverse osmosis (RO) membrane systems are widely used in water purification plants. Reduction in plant performance due to biofilm formation over the membrane is an inherent problem. As quorum sensing (QS) mechanisms of microorganisms have been reported to be involved in the formation of biofilm, ways are sought for quorum quenching (QQ) and thereby prevention of biofilm formation. In this study using a chemostat culture run for seven days in a CDC reactor it was found that a natural QQ compound, vanillin consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…These results suggested that biofilms formed in the presence of a chloroform extract were loosely attached to microtiter plate surfaces and removed easily by the treatment of the surfactant, as compared with biofilms formed in the absence of chloroform extracts. This potential of biofilm inhibitors can be used in industries to remove biofilms formed on membrane filters during the treatment of water (Kappachery et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that biofilms formed in the presence of a chloroform extract were loosely attached to microtiter plate surfaces and removed easily by the treatment of the surfactant, as compared with biofilms formed in the absence of chloroform extracts. This potential of biofilm inhibitors can be used in industries to remove biofilms formed on membrane filters during the treatment of water (Kappachery et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Phloretin has various biological functions, such as antioxidative (36), anticarcinogenic (50), and estrogenic (6) activities and inhibition of cardiovascular disease (10,41). Recently, several other flavonoids showed the ability to inhibit the biofilm formation of Streptococcus mutans (22), Aeromonas hydrophila (18), and Escherichia coli O157:H7 (48). Additionally, a transcriptome analysis demonstrated that apple polyphenols, including phloretin, possessed anti-inflammatory effects against inflammatory bowel diseases (IBDs) in vitro (17).…”
mentioning
confidence: 99%
“…isolates from both trout and tilapia (Tables 2 -3). Vanillin did not demonstrate an antimicrobial effect against the fish pathogen Aeromonas hydrophila at concentrations ranging from 63 -250 µg/ml but rather inhibited quorum sensing and biofilm development (Kappachery et al, 2010), thus attenuating its pathogenicity. Fitzgerald et al (2004) observed that vanillin had a time of exposure, concentration and speciesspecific dependency to its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Vanillin (4-hydroxy-3-methoxybenzaldehyde) is a major component of natural vanilla, obtained from the bean of the tropical orchid Vanilla planifolia (Kappachery et al, 2010). The inhibitory action of vanillin on E. coli, Lactobacillus plantarum and Listeria innocua cells was due to its ability to negatively affect cell membrane integrity, which resulted in a loss of the ion gradient, pH homeostasis and an inhibition of respiration (Fitzgerald et al, 2004).…”
Section: Discussionmentioning
confidence: 99%